STUDY OF STUDENT KNOWLEDGE ON THE IMPACT OF FAST FOOD IN THE MIDWIFERY ACADEMY OF TAHIRAH AL BAETI BULUKUMBA - Erniawati; Ika Handayani; Nurfadillah; Riska Y (Akademi Kebidanan Tahirah Al Baeti Bulukumba, 2019)
Fast food is chosen because it is served fast so it saves times and can be served anytime and anywhere, a hygienic serving and serving place, is considered prestigious food, modern food, as well as slang food for young people. In Indonesia it has been found with certainty, but research conducted by the Directorate of Community Nutrition, the ministry of Health of the Republic Of Indonesia, recorded an estimated 210 million people in Indonesia in 2000, the number of people who are overweight is estimated to be 76,7 million people and obese people are more than 9.8 million. To find out how student knowledge about the impact of fast food in Akbid Tahirah Al Baeti Bulukumba. This type of research is a type of qualitative research with a total sample of 48 people and the sampling technique is total sampling. Of the 48 respondents there were students who had good knowledge as many as 43 students (89,58%), students who had sufficient knowledge were 4 students (8,33%), and students who had less knowledge were 1 student (2,09%). Most of the respondents have good knowledge as many as 43 people about the impact of fast food on Akbid Tahirah Al Baeti Bulukumba